Kejahatan Seksual dan Paradigma Victim-Centered Justice dalam Hukum Pidana Indonesia - Kholidazia El Hamzah F.; Hasan Basri; Samsul Huda; Abdur Rohim (Jurnal Hukum Lex Generalis, 2026)
Sexual crimes inflict prolonged physical, psychological and social impacts on victims. Indonesia's criminal law reform through the Law on Sexual Violence Crimes and the National Criminal Code (KUHP) demonstrates a paradigm shift toward victim protection through a victim-centered justice approach. This article analyzes the implementation of this paradigm in handling sexual crimes in Indonesia. The findings indicate that although the normative framework has accommodated the victims' interests and rights, judicial practices still face challenges in the form of secondary victimization. Furthermore, a gap remains between statutory regulations and their enforcement by law enforcement authorities in providing effective protection to victims. Therefore, it is necessary to formulate and implement standard operating procedures (SOPs) oriented toward victim protection and recovery at every stage of the criminal justice process.